Answer:
Perpendicular means that,second gradient equals to first one as:
![- (1)/(m)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5rmxvoyfddd8i0wf95fstybvpq3cly9z4v.png)
So,conducting the second equation to the form y=mx+c: 3y= -2x-5
![y = - \frac {2}{3}x - (5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zsuo824a3x6w7v2hd8gizbn1lk5mkvx6ya.png)
So it's gradient is
![- (2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zmfkg6ozk7tj7qwdzixswtjfasyeihs2q6.png)
converting to
![- (1)/(m)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5rmxvoyfddd8i0wf95fstybvpq3cly9z4v.png)
equals to 1.5 or at least
![(3)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/85tww783zdtzzps1k74cyql3cl3s1y42ha.png)
Y find the equation of the first line you've got to use the formula: y-y1=m (x-x1)
y-1=1.5 (x+6)
y-1=1.5x+9
y=1.5x+10 is the equation of the first line.